(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Women’s property rights in India have witnessed a long and complex journey, shaped by cultural traditions, religious prescriptions, colonial interventions, and post-independence constitutional and legislative reforms. From the restrictive notions of Stridhana in ancient Hindu law to the revolutionary Hindu Succession (Amendment) Act, 2005, the trajectory reflects both the resilience of patriarchy and the struggle for gender justice. This article explores the evolution of women’s property rights in India across different historical phases, critically examining how ancient customs, medieval traditions, colonial codifications, and modern legal frameworks have influenced women’s access to property. It also highlights judicial interpretations and constitutional principles that continue to push for equality in ownership and inheritance.